POLA KOMUNIKASI ORANG TUA KEPADA ANAK TERHADAP PELANGGARAN ADAT LARANGAN PERNIKAHAN SESAMA SUKU (STUDI FENOMENOLOGI TERHADAP ADAT LARANGAN PERNIKAHAN SESAMA SUKU TANJUNG DIMINANGKABAU LUBUK BASUNG SUMATERA BARAT): STUDI FENOMENOLOGI TERHADAP ADAT LARANGAN PERNIKAHAN SESAMA SUKU TANJUNG DIMINANGKABAU LUBUK BASUNG SUMATERA BARAT - Werliana, Hesti; yenrizal; Citra Hati, Putri (Jurnal Prodi Ilmu Komunikasi, 2024)
This study aims to find out and analyze the meaning of communication patterns between parents and children from the communication process of couples who are married to fellow Tanjung tribes in Minangkabau, Lubuk Basung, West Sumatra. Communication is a form of foundation that cannot be separated from humans as social beings. This research focuses on knowing how the communication patterns of parents towards children who violate the customary prohibition of same-ethnic marriage and can understand the values ​​contained in the customary prohibition of same-ethnic marriage. In this study using descriptive qualitative methods with data collection techniques in the form of observation, interviews and documentation. The informants in this study were couples who married the same tribe and parents of couples who married the same ethnic group, namely three parents of children who violated adat and three couples who violated the customary prohibition of same-ethnic marriage. This research is based on phenomenological theory. The results of the study show that actually marriage has become something that must be done by lovers, but in the custom of same-tribe marriage this has its own uniqueness in Minangkabau custom, namely couples are prohibited from marrying even though they are not siblings. This is something that can change the pattern of communication between children and parents. Changes in children's communication patterns with their parents can be seen from before the couple got married where the couple who violated the custom were very close to the family and there were no obstacles in communicating with the family. Then after they get married the communication that occurs between parents and children is inversely proportional before they get married. After they got married, the couple found it very difficult to communicate with their family because the couple had to obey the customary law in Minangkabau, Lubuk Basung, West Sumatra.